Potential Relationship between ABO Blood Group and COVID-19 Susceptibility - Shalal, Sara Kareem (South Eastern European Journal of Public Health, 2024)
Numerous research have looked into the potential relationship between blood group systems and the severity of COVID-19, with varying degrees of success. However, depending on how common the Rh and ABO blood types are in a given community, their correlations with COVID-19 may also vary. Thus, in order to explore this relationship more thoroughly and give population-based data to the global scientific community, we carried out this study on Iraqi people. Methodology: Every patient who arrived at Al-Shatra General Hospital in the province of Thi-Qar between December 2022 and June 2023 had their data examined. One hundred participants, ranging in age from eighty to eighty, made up the study. Their hospital medical records were used to determine their ABO, Rh type, and COVID-19 positive. Result: The total number of patients was 100, and males constituted 56% of this population. Among the 100 patients, 19% were diagnosed with diabetes mellitus while 34% had hypertension. From the findings, it was noted that A+, B+, and O+ blood types had more occurrences of COVID-19 positive cases. Interestingly, the percentage of individuals testing positive for COVID-19 was higher at 58% among those with hypertension and lower at 42% among those with diabetes mellitus. Conclusions: The relationship between blood types and COVID-19 infection is a multifaceted dynamic that encompasses various factors, including comorbidities, age, sex, and the distribution of blood groups within a population. It has been observed that individuals with hypertension are more prone to experiencing elevated rates of COVID-19.